The Question of the A̶n̶i̶m̶a̶l̶ Great Blue Heron: Review of Steven H. Semken, Soul External: Rediscovering the Great Blue Heron - Sax, Boria (Humanimalia, 2015)
Steven H. Semken. Soul External: Rediscovering the Great Blue Heron. Illustrations and design by Andrew R. Driscoll. North Liberty, IA: Ice Cube Press, 2015. 139 pp., $24.95 hc.